Oral Verrucous Carcinoma: A Study of 12 Cases - Alkan, Alper; Bulut, Emel; Gunhan, Omer; Ozden, Bora (European Journal of Dentistry, 2010)
Objectives: The purpose of this clinical study was to identify a clinical and histopathological relationship between verrucous hyperplasia, verrucous keratosis, and verrucous carcinoma.Methods: We evaluated 12 patients who had developed oral verrucous carcinoma in the past 10 years in a follow-up study. In this study, the diagnostic criteria included clinical and histopathological features of the lesions. Each lesion was examined by a single oral pathologist.Results: All the patients were diagnosed with verrucous carcinoma following excisional biopsy. One patient was diagnosed with verrucous hyperplasia and another with verrucous keratosis in their initial histological findings. Mandibular, posterior alveolar crest, and retromolar trigone were the most affected sites (41.6%), followed by the buccal mucosa (16.6%), the palate (16.6%), the floor of the mouth (16.6%), and the lip (8.3%). No patients had evidence of recurrence after treatment.Conclusions: Verrucous hyperplasia, verrucous keratosis, and verrucous carcinoma may not be distinguished clinically or may coexist, resulting in diagnostic difficulties. It should be kept in mind that verrucous hyperplasia may also develop from leukoplakic lesions, and it may transform into verrucous carcinoma or squamous-cell carcinoma, acting as a potential precancerous lesion. (Eur J Dent 2010;4:202-207)
Keywords: Oral; Verrucous carcinoma; Verrucous hyperplasia; Verrucous keratosis